2017
DOI: 10.1200/jco.2016.67.4119
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Best Treatment of Locally Advanced Nasopharyngeal Carcinoma? An Individual Patient Data Network Meta-Analysis

Abstract: Purpose The role of adjuvant chemotherapy (AC) or induction chemotherapy (IC) in the treatment of locally advanced nasopharyngeal carcinoma is controversial. The individual patient data from the Meta-Analysis of Chemotherapy in Nasopharynx Carcinoma database were used to compare all available treatments. Methods All randomized trials of radiotherapy (RT) with or without chemotherapy in nonmetastatic nasopharyngeal carcinoma were considered. Overall, 20 trials and 5,144 patients were included. Treatments were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
221
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 279 publications
(236 citation statements)
references
References 47 publications
9
221
2
4
Order By: Relevance
“…Targeted therapies such as TKIs are showing promising clinical efficacy in cancer patients, however, the side effects of the therapy can in some cases adverse symptoms that may lead to the cessation of treatment . A very common adverse effect from chemotherapy or certain TKIs, such as neratinib, is diarrhea which can lead to dramatic loss of fluids and electrolytes, and under severe conditions also lead to malabsorption of nutrients due to the accelerated transit time along the intestine …”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapies such as TKIs are showing promising clinical efficacy in cancer patients, however, the side effects of the therapy can in some cases adverse symptoms that may lead to the cessation of treatment . A very common adverse effect from chemotherapy or certain TKIs, such as neratinib, is diarrhea which can lead to dramatic loss of fluids and electrolytes, and under severe conditions also lead to malabsorption of nutrients due to the accelerated transit time along the intestine …”
Section: Discussionmentioning
confidence: 99%
“…The analyses by the MAC‐NPC Collaborative Group favored additional chemotherapy . The comparisons of concurrent chemotherapy were more heterogeneous: a review of individual trials showed that only the trial using concurrent cisplatin for patients largely with stage II disease treated by 2‐dimensional RT achieved significant benefits for both PFS and OS .…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes were overall survival, progression‐free survival, locoregional control, and distant control. For each outcome, the authors ranked the treatments by P scores, here given in Table . P scores are numbers between 0 and 1, with mean 0.5, representing the rank of a treatment within the given range of competing treatments, where 1 means theoretically best and 0 means worst .…”
Section: Data Setsmentioning
confidence: 99%